Expression of vascular endothelial growth factor (VEGF) and its receptor (VEGFR) in thyroid nodular hyperplasia and papillary thyroid carcinoma (PTC) - Razy, Nur Hidayati Mohamad Pakarul (2017)
ABSTRACT Background and objective: Vascular endothelial growth factor (VEGF) is an angiogenic factor that plays important role in tumour growth with ongoing research regarding its role as a prognostic factor and also targeted anti-angiogenic therapeutic agent in thyroid cancer. VEGF is known to have high affinity to VEGF receptors such as VEGFR-1 (Flt-1) and VEGFR-2 (KDR) and their co-expression in pathological condition had been demonstrated in previous studies. Papillary thyroid carcinoma (PTC) is the most common differentiated thyroid cancer and studies showed the increasing incidence of carcinoma arising in multinodular goitre (MNG). The aim of the current study to determine the expression of VEGF and VEGF receptors (VEGFR) in thyroid nodular hyperplasia and PTC. Materials and methods: We conducted a cross sectional study based on retrieved paraffinized archival tissue blocks of 113 nodular hyperplasia and 67 PTC from the thyroidectomy specimens from the year of 2003 to 2014.The tissue sections were then stained by immunohistochemistry for VEGF, VEGFR-1 and VEGFR-2. The lymph node involvement and extrathyroid extension also were determined. Results: The mean age of PTC patients was 44.7 ± 15.8years and nodular hyperplasia subjectswere42.2 ± 13.6years. Female gender predominate in both benign nodular hyperplasia and PTC with, 86% (97 out of 113) and 78% (52 out of67) respectively. There was a statistical difference of VEGFR-1 (p=0.028) andVEGFR-2 (p=0.003) expression between nodular hyperplasia and PTC. However, no significant difference of VEGF expression (p=0.576) between both diseases. Co-expression of VEGF and VEGFR-1 was significant in both nodular hyperplasia (p=0.016) and papillary thyroid carcinoma (p=0.03), meanwhile no relevant relationship for VEGF and VEGFR-2 expression (p>0.05). The patients were further divided into young age group (<45 years old) and older age group (≥45 years old). Most of the subjects positive for lymph node metastasis and had extrathyroid extension were female and from older age group. From 15 lymph nodes with metastasis, 60% (9/15) were female and 53% (8/15) from older age group. All two cases that showed extrathyroid extension were from older age group and female. However, there was no significant association (p>0.05) between lymph node status and extrathyroid extension with age groups, gender, VEGF and VEGFR expression. Conclusions: VEGF, VEGFR-1 and VEGFR-2 showed overexpression in both benign thyroid nodular hyperplasia and PTC. The expression of VEGFR-1 and VEGFR-2 more significant in PTC with relevant co-expression of VEGF and VEGFR-1.